Juridical Review Regarding the Accountability of Police Investigators in the Case of Wrongful Arrest - Mulya, Isal; Lesmana, Sri Jaya; Ayu Lestari, Tiara (The International Journal of Law Review and State Administration, 2024)
The sense of justice and basic rights of Indonesian citizens is a central part that is upheld in recognition and existence. As a state of law, Indonesia views the position of all citizens equally without exception. The position of law is accepted as an ideology that is expected to create justice, security, order, and realize state welfare. The police as a state apparatus carry out the task of carrying out law enforcement, where one of its duties is to investigate a case. Cases of misapprehension that have been rife lately have unfavorable implications in law enforcement. The purpose of this research is to find out the factors and how the form of accountability for the occurrence of the misapprehension. The method of normative juridical approach becomes the method used in research. The results showed that there were several factors that caused police investigators to make false arrests which were essentially related to work professionalism. This is clearly detrimental to victims and also law enforcement that is running. The responsibility of the police investigator in this case if the victim makes pretrial legal remedies, it can be processed to stop the investigation and/or prosecution. But in the event that the victim does not file a legal remedy so that the case then proceeds with the process.